2016
DOI: 10.1103/physrevb.94.165313
|View full text |Cite
|
Sign up to set email alerts
|

Phonon-dressed two-dimensional carriers on the ZnO surface

Abstract: Two-dimensional (2D) metallic states formed on the ZnO(1010) surface by hydrogen adsorption have been investigated using angle-resolved photoelectron spectroscopy (ARPES). The observed metallic state is characterized by a peak-dip-hump structure at just below the Fermi level and a long tail structure extending up to 600 meV in binding energy. The peak and hump positions are separated by about 70 meV, a value close to the excitation energy of longitudinal optical (LO) phonons. Spectral functions formulated on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
(75 reference statements)
2
24
0
Order By: Relevance
“…The transition would then appear around 3.8 × 10 12  cm −2 , slightly below the density reported in ref. 9. In agreement with our estimate, the spectra of ref.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The transition would then appear around 3.8 × 10 12  cm −2 , slightly below the density reported in ref. 9. In agreement with our estimate, the spectra of ref.…”
Section: Discussionsupporting
confidence: 92%
“…The interest in electron–phonon coupling and polaronic quasiparticles in TMOs has been reinvigorated by recent angle-resolved photoelectron spectroscopy (ARPES) experiments 5 6 7 8 9 . The signature of polaronic behaviour in ARPES spectra is the appearance of satellites below the conduction band, at integer multiples of the optical phonon energy.…”
mentioning
confidence: 99%
“…We deduce an Eliashberg coupling function wholly compatible with a 2D Debyelike distribution of phonons and a mass enhancement parameter λ = 0.3.Previous photoemission experiments on ZnO [35][36][37][38][39][40][41] showed that hydrogenation of its polar or non-polar surfaces, for instance through chemisorption of hydrogen, methanol or water, induces a downward band-bending and the formation of a 2DES with a moderate electron density n 2D ≤ 2 × 10 13 cm −2 , showing only one broad shallow subband below the Fermi level (E F ) [40]. More recently, several ARPES studies focused on the manybody phenomena of electron-phonon coupling in oxides, demonstrating that at low carrier densities the 2DES in TiO 2 , SrTiO 3 and also ZnO are composed of polarons [42][43][44]. Due to a non-adiabatic electron-phonon coupling, the polaronic regime changes to a Fermi liquid behavior with increasing electron densities, as electronic screening of the polar lattice becomes more efficient [45].…”
mentioning
confidence: 99%
“…Evidence of Fröhlich polarons was found also from the investigation of two-dimensional (2D) electronic states at the surfaces or interfaces of oxides, with the most studied case being the 2D electron gas (2DEG) formed at the surface of SrTiO 3 [7,51,52]. Other notable examples are the 2DEG at the interface between SrTiO 3 and LaAlO 3 [53] and on the surface of ZnO [54]. The experiments also show a remarkable evolution of the carriers with doping concentration, from polarons to a Fermi liquid weakly coupled to phonons [6,7].…”
Section: Polaron Satellites In Doped Semiconductorsmentioning
confidence: 95%